The Gender Gap in Wages over the Life Course: Evidence from a British Cohort Born in 1958 - Heather Joshi; Alex Bryson; David Wilkinson; Kelly Ward (Institute of Labor Economics (IZA), 2019)
Using data tracking all those born in a single week in Great Britain in 1958 through to their mid-50s we observe an inverse U-shaped gender wage gap (GWG) over their life- course: an initial gap in early adulthood widened substantially during childrearing years, affecting earnings in full-time and part-time jobs. In our descriptive approach, education related differences are minor. Gender differences in work experience are the biggest contributor to that part of the gender wage gap we can explain in our models. Family formation primarily affects the GWG through its impact on work experience. Family composition is similar for male and female workers but attracts opposite wage premia. Not all of the GWG however is linked to family formation. There was a sizeable GWG on labour market entry and there are some otherwise unexplained gaps between the pay of men and women who do not become parents.
Keywords: J16; J31; 330; family formation; gender wage gap; work experience; life course; NCDS birth cohort